2005
DOI: 10.2310/6350.2005.31309
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Endovenous Treatment with an 810 nm Laser versus Conventional Stripping of the Great Saphenous Vein in Patients with Primary Varicose Veins

Abstract: The endovenous great saphenous vein photocoagulation is safe and well tolerated and presents results comparable to those of conventional stripping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 54 publications
1
34
0
2
Order By: Relevance
“…15 The safety of EVLT and its efficacy in the early postoperative phase seem to be comparable with those of conventional surgery, as shown by recent randomized controlled trials (RCTs). [16][17][18][19][20][21] Although the procedure is considered to be highly variable in terms of wavelength, mode of application, power, and energy dose, EVLT is deemed to be safer and more effective compared with radiofrequency obliteration and ultrasonography-guided foam sclerotherapy. 14,22 However, there is still a medical need for further RCTs comparing endovenous techniques with standard surgical treatment of saphenous vein incompetence to drive reliable conclusions, particularly concerning clinical efficacy.…”
mentioning
confidence: 99%
“…15 The safety of EVLT and its efficacy in the early postoperative phase seem to be comparable with those of conventional surgery, as shown by recent randomized controlled trials (RCTs). [16][17][18][19][20][21] Although the procedure is considered to be highly variable in terms of wavelength, mode of application, power, and energy dose, EVLT is deemed to be safer and more effective compared with radiofrequency obliteration and ultrasonography-guided foam sclerotherapy. 14,22 However, there is still a medical need for further RCTs comparing endovenous techniques with standard surgical treatment of saphenous vein incompetence to drive reliable conclusions, particularly concerning clinical efficacy.…”
mentioning
confidence: 99%
“…No difference in safety including the risk of venous thromboembolism could be determined, comparing EVTA and surgical treatment for saphenous vein incompetence. 367,391 The reported incidence of DVT varies between 0.2% and 1.3% in EVTA, and seems to be higher in patients treated with RFA compared with EVLA. 357 The latter meta-analysis mainly included the old RFA techniques and EVLA with bare tip fibres and lower wavelength.…”
Section: Endovenous Thermal Ablationmentioning
confidence: 99%
“…356,365,369,374,377,378 Post EVTA as opposed to surgery, swelling and bruising is reduced. 391 This results in quicker recovery 357,362,375,376 and faster return to normal activities. 364,365,374,378,392 Endovenously treated patients also seem to have an equal 364,366,367 or better 361 QoL after treatment.…”
Section: Endovenous Thermal Ablationmentioning
confidence: 99%
“…Comparative studies in which the outcomes of patients undergoing classic vein stripping (CVS) and EVLA were analyzed revealed that the latter experienced lower postoperative pain and bleeding, decreased frequency of wound infections and hematoma, and shorter time of convalescence [6, 7]. Literature is, however, not fully consistent in this regard, as there are also reports in which some postintervention effects of both kinds of surgery (e.g., pain, thrombosis, and bleeding) were comparable [7, 8]. …”
Section: Introductionmentioning
confidence: 99%